The Relationship Between Personal Hygiene with Hepatitis a Incident in Students - Sasoka, Dwika Sari; Satyabakti, Prijono (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTThe prevalence and distribution of Hepatitis A in Indonesia had been increased over past few years. It resulted in the endemic status of Hepatitis A in Indonesia. The purpose of this research is to analyze the relationship between personal hygiene and Hepatitis A incidence in Jember. This study use a case-control design, with quantitative approach using primary data. Population of this study is student that has been randomize using simple random sampling for case group and purposive random sampling for control group. Respondents of this study is 15 for case group and 30 for control group. Idependent variable of this study is personal hygiene behaviour. Analysis are performed using Chi-Square test and Odd Ratio (CI = 95%). The study showed that majority case group have poor personal hygiene (53,3% respondents) and majority of control group have healthy personal hygiene (83,3% respondents). There is a significant relationship (p= 0,016) between personal hygiene with the incidence of Hepatitis A. Personal hygiene is the risk factor of Hepatitis A incidence, OR = 5,71 (95% CI: 1,17â29,88). The conclusion is there is a relationship between personal hygiene with Hepatitis A incidence. In order to increase awareness of personal hygiene to prevent Hepatitis A, is by using eating and drinking equipments proprietary, washing hands with soap before meals and after defecating, drinking boiled water and buy food in hygiene and sanitary food vendors.Keywords: Hepatitis A, personal hygiene, students, risk factor, case control